Professoras das escolas comunitárias luteranas no Brasil: uma ciranda histórico-feminista da educação - SANDER, Franciele Vanessa (2022)
The ciranda is an image used by the feminist theologian Elizabeth Schüssler Fiorenza to represent her form of research, in which there is no hierarchy or power, because all people are equal in the circle. In the present research, this image is used as a symbol of her writing, in which she seeks to analyze the influence of the feminization process in the EvangelicalLutheran communitarian schools linked to the Synodal Education Network, aiming at identifying the period and context in which the entrance of women into the Evangelical Seminary of Teacher's Formation in Rio Grande do Sul occurred, and its reasons; and, to historicize the process of the feminization of teachers in communitarian schools, giving voice to its protagonists. We started from the verification of a gap regarding the record of the presence of women in the historical texts of the mentioned schools, and, despite the few reports, there are reasons, that lead to the suspicion, from the perspective of the feminist hermeneutics, that women would be present in a more active way than what is observed in the bibliographies analyzed regarding this topic. Initially, the relevance of the study of our object is discussed, followed by a historical review to understand the identity complexity of the ethnic group on which it will focus. Next, we seek to understand the nuances of the education of teachers in the Evangelical Seminary and the participation of women in this space. Then, the stories of women teachers and their work contexts are told. We conclude by identifying the closing moment of the ethnic schools, placing it in the period of the nationalization of teaching in the Vargas Era. To this end, the research is qualitative in nature, documental carried out in the Historical Archive of the Evangelical Church of Lutheran Confession in Brazil and bibliographic; having the theoretical contributions of: Altmann (1991), Dreher (1984, 1992), Deifelt (2003), Dubar (2020), Kreutz (2000), Meyer (2000), Nunes (2006), Scott (1989), Streck (1997) and Yannoulas (2011). The research is situated in the field of History of Education with the Feminist Theology for its relationship with gender studies. The methodological key that feminist theology uses for reading is the feminist hermeneutic of suspicion that is used as a criterion for data collection and analysis. In this research, some women who worked as teachers were discovered. These were named, along with their stories, and were historically placed, linking them to their training and performance spaces. This dissertation intends to add to the studies that seek to give visibility to the presence of women in the Brazilian teaching profession, making a record of their working in spaces in which there was silencing as to their teaching practice.